Arctic Sea Ice Decline Preconditions Events of Anomalously Low Sea Ice Volume Export Through Fram Strait in the Early 21st Century. Issue 2 (2nd February 2021) - Wang, Qiang; Ricker, Robert; Mu, Longjiang
Abstract: Understanding the changes of Fram Strait sea ice volume export and responsible processes is crucial due to their climate relevance. In this paper, we disentangled the processes driving the interannual variability and trends of the Fram Strait sea ice volume export in the early 21st century (2001–2019) by using dedicated numerical simulations with the support of observations. The significant decreasing trend in the sea ice volume export is caused by the persistent thinning trend of Arctic sea ice, while the interannual variability of the volume export is predominantly determined by winds. The interannual variability of the volume export can be mainly attributed to the variation in sea ice drift at Fram Strait, while the variation in Fram Strait sea ice thickness also plays an important role. As a result, the atmospheric mode that can better represent the wind variability driving the variability of both the sea ice drift and thickness at Fram Strait can better explain the variability of the sea ice volume export. The wintertime Arctic Oscillation (AO) and Fram Strait sea ice volume export continue to have a strong linkage in the early 21st century. The persistent thinning of Arctic sea ice preconditions events of anomalously low Fram Strait sea ice volume export. One of the extreme events in recent years occurred in 2017/2018. Variation in winds alone would not have caused such an extreme event without the persistent Arctic sea ice thinning. Plain Language Summary: A strong freshening in the upper ocean of the northern North Atlantic was observed in the 1970s. This event was caused by very high export of sea ice volume through Fram Strait at the end of the 1960s and was the first well‐documented Great Salinity Anomaly (GSA). GSAs can have strong impacts on the ocean circulation in the North Atlantic and may also affect weather. With persistent sea ice thinning in the Arctic Ocean, the export of Arctic sea ice through Fram Strait into the North Atlantic has fallen significantly in the early 21st century. An extreme event of very low sea ice volume export through Fram Strait in recent years is found in this study. This event is due to a combination of winds that tend to reduce sea ice export and the ongoing thinning of Arctic sea ice over past decades. As we expect that Arctic sea ice will continue to decline in a warming world, even stronger events can be anticipated later. Will such events of low sea ice export cause a "positive" GSA, with higher surface salinities in the northern North Atlantic and significant impacts on ocean circulation? This remains to be better monitored and understood. Key Points: Arctic sea ice thinning causes a significant decreasing trend in sea ice thickness and volume export at Fram Strait Arctic sea ice thinning preconditions events of anomalously low Fram Strait sea ice volume export Sea ice volume export over 2001–2019 has close linkages with the Arctic Oscillation in winter and with the Dipole Anomaly for annual means